The Wired City : Reimagining Journalism and Civic Life in the Post-Newspaper Age - Kennedy, Dan, 1956- (Book collections on Project MUSE., 2013)
This book tells the story of the New Haven Independent, a nonprofit community website in Connecticut that is at the leading edge of reinventing local journalism. Through close attention to city government, schools, and neighborhoods, and through an ongoing conversation with its readers, the Independent's small staff of journalists has created a promising model of how to provide members of the public with the information they need in a self-governing society. At a time of pessimism over the future of journalism, this book offers hope. What the author documents is not the death of journalism, but rather the uncertain and sometimes painful early stages of rebirth.